Retraction Note: The Evaluation of Reactor Performance by Using Flibe and Flinabe Molten Salts in the APEX Hybrid Reactor - Korkut, Turgay; Hançerlioğulları, Aybaba (Springer Science and Business Media LLC, 2012)
The modeling of APEX hybrid reactor, produced by using ARIES-RS hybrid reactor technology, has been performed by using the MCNP-4B computer code and ENDF/B-V-VI nuclear data. Around the fusion chamber, molten salts Flibe (Li2BeF4) and Flinabe (LiNaBeF4) were used as cooling materials. APEX reactor was modeled in the torus form by adding nuclear materials of low significance in the specified percentages between percent 0–12 to the molten salts. The result of the study indicated that fissile material production, UF4 and ThF4 heavy metal salt increased nearly at the same percentage and it was observed that the percentage of it was practically the same in both materials. In order for the hybrid reactor to work itself in terms of tritium, TBR (tritium breeding ratio) should be lower than 1.05. When flibe molten salt was utilized in the APEX hybrid reactor, TBR was calculated as >1, 22 and when flinabe molten salt was used, TBR was calculated as >1.06.
Keywords: 7. Clean energy